Geochemical assessment of some natural waters from eastern and south-eastern Macedonia - Šijakova-Ivanova, Tena; Ambarkova, Vesna (Geologica Macedonica, 2015)
The paper deals with short review and determination of macro-, micro-, trace and ultratrace elementsin some natural waters from еastern and сouth-eastern Macedonia. In our study were investigated 16 samplesof natural waters from the villages Trabotivište near the city of Delčevo, Istibanja near Kočani, Neokazi near Probištip,Plačkovica, Karaorman, Gorni Balvan and Lakavica near Štip, Jargulica near Radoviš, Murtino, Robovo, Gabrovoand Smolare near Strumica. Obtained results showed that most of the analyzed elements in all selected watersamples were below the Macedonian maximum allowable levels and WHO water standards. Increased concentrationsof some elements indicate anthropogenic pollution of the water from the fertilization of arable land, livestock farms.There is a strong positive correlation between Ca → SO4, Na, Mg; Ti → Ca, Mg, Na, K, B; U → Mo, Rb, Cs, As; B→ Ca, Ti, Ge, Cl, HCO3; Li → Mg, Na, K, B, Sr, Rb; Ge → Ca, Mg, Na, B, Ti, Li, Cl, Pb; Cl → Mg, Na, K, B, Sr,Li, Pb; HCO3 → Ca, Mg, Na, K, B, Ti, Sr, Li, Pb, Co, Se, Ge; NO3 → Na, Sr, Li, Pb, Cs, Se; SO4 → Na; TDS → EC.According to the obtained values for total hardness, investigated waters are hard, moderately hard and very hard.High values for total hardnes sare mainly due to solubility of carbonate rocks. Positive CAI values noted in Neokazi(samples 1 and 2), Jargulica (samples 1 and 2), Novo Selo, Murtino, Robovo, Gabrovo and Smolare suggest that sodiumand potassium from water are exchanged with magnesium and calcium in rock following base exchange reactions(chloro-alkaline equilibrium), whereas negative CAI values noted at Trabotivište, Istibanja, Karaorman Plačkovica,Lakavica (samples 1 and 2) suggest that magnesium and calcium from water are exchanged with sodium andpotassium in rocks favouring cation-anion exchange reactions (chloro-alkaline disequilibrium). After Piper diagramthe type of water in the study area is mainly calcium/magnesium bicarbonate and are most likely result of the compositionof the geological environment through which the water flows where this natural water circulates. Knowing thenatural water quality of the research area is of particular importance because these waters are used by the residents ofthis region as drinking water and for irrigation.